Exploratory study on the utilization of different dietary methionine sources and methionine to lysine ratio for growing-finishing pigs - Remus, Aline [UNESP]; Peres, Francine Mendes [UNESP]; Hauschild, Luciano [UNESP]; Andretta, Ines [UNESP]; Kipper, Marcos; de Paula Gobi, Jaqueline [UNESP]; Pomar, Candido (Elsevier, 2015)
The objective of this meta-analysis was to evaluate the response of growing-finishing pigs to different dietary methionine sources and to determine the ideal methionine:lysine ratio for nursery to finishing pigs. Data were obtained from peer-reviewed journals. Information were extracted from the material and methods and results sections of pre-selected articles. Forty one articles were included in the first database. Graphical and correlation analyses, multivariate exploratory analysis of factors, variance-covariance analysis, and non-linear models were applied to estimate nutritional requirements. Eighty-three percent of the articles in the database were not used for the determination of the methionine:lysine ratio because the diets did not meet the pigs' lysine requirements. Methionine sources were compared using 21 articles of the first database, and performance differences were not found (P<0.05) among pigs fed diets containing l-methionine, dl-methionine, or methionine hydroxy analog. The ideal methionine:lysine ratio calculated for maximum performance of growing-finishing pigs was 26%. In this meta-analysis, studies carried out since 1964 on pig methionine requirements were reviewed, suggesting the standardization of experimental protocols to allow better comparison among the studies. On the basis of the outcome of this study, it allowed the evaluation of different methionine sources were they promoted similar performance in nursery piglets and to determine minimum methionine:lysine ratios for pigs, from nursery to finishing, that was calculated as 26% methionine as a function of lysine requirement.
Keywords: Amino acids; Meta-analysis; Nutrition; Requirements; Swine